INFLUANCY OF PHLOTOREAGENT «OIB IBS» ON CONDITION OXIDATION-RESTORING PROCESSES OF WARM–BLOODED ANIMALS - Sirenko, E.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The condition of oxidation-restoring processes of white rats in prasence of phlotoreagent was studied insubcute experiment. The statisticaly trustworthy datas of activity membranospecific lipidodepended enzymesand transport ATPH-acid of blood and tissues of white rats was registered. The degree of dependence of biochemical datas disoders from doses of organic substance was revealed. Experimental datas confirms thefact of disoders bioenergetic processes of cells and negative influance of phlotoreagent «OIB IBS» onoxidation-restoring processes in organism of warm-blooded animals.